2010
DOI: 10.1590/s1676-24442010000200003
|View full text |Cite
|
Sign up to set email alerts
|

Comparação entre dois métodos de detecção de DNA de papilomavírus humano em carcinoma epidermoide de lábio

Abstract: Introdução: Recentemente o papilomavírus humano (HPV) tem sido associado à carcinogênese oral. A metodologia empregada na detecção do vírus é uma das maiores causas observadas da grande variabilidade nas taxas de detecção do HPV. Objetivo: Este estudo comparou a sensibilidade de detecção do DNA do HPV em casos de carcinoma epidermoide de lábio utilizando a amplificação do DNA viral por reação em cadeia da polimerase (PCR) ou nPCR. Material e método: Foram utilizadas 33 amostras provenientes de casos de carcino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
0
6
0
1
Order By: Relevance
“…Studies in the literature indicate variables rates of HPV detection. This differences in detecting DNA of HPV suggest a potential difference in the ability to amplify fragments of different sizes and specific types of HPV, depending on the methods used for DNA detection, and may also de due to the types of studied material (smears, frozen material, paraffin material), anatomical localization, population issue, and design of oligonucleotides (5) . In this study we observed a greater number of positive samples using GP5+/GP6+ oligonucleotides, when compared to MY09/ MY11.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in the literature indicate variables rates of HPV detection. This differences in detecting DNA of HPV suggest a potential difference in the ability to amplify fragments of different sizes and specific types of HPV, depending on the methods used for DNA detection, and may also de due to the types of studied material (smears, frozen material, paraffin material), anatomical localization, population issue, and design of oligonucleotides (5) . In this study we observed a greater number of positive samples using GP5+/GP6+ oligonucleotides, when compared to MY09/ MY11.…”
Section: Discussionmentioning
confidence: 99%
“…The choice of suitables oligonucleotides to clinical and epidemiological uses should consider the source of clinical material, the size of PCR product, range of DNA-HPV types to be amplified, oligonucleotides ability to amplify the HPV multiple types and the availability of sequencers systems or specific probes to identifying the different HPV genotypes (5) .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the n-PCR technique was used, which combines two diVerent pairs of consensus primers. The advantage of this last technique is the substantial increase in sensitivity [10,15]. However, we cannot exclude the possible contribution of still undeWned genetic factors in the diVerent populations studied.…”
Section: Discussionmentioning
confidence: 94%
“…These samples were analyzed using the polymerase chain reaction (PCR) technique in the Advanced Laboratory of Public Health (LASP) of FIOCRUZ in Salvador, Brazil. For DNA ampliWcation, it was used the nested PCR (n-PCR) method, as suggested by Demathe et al [10] with some modiWcation. For the Wrst round, it was used the MY09/11 consensus outer primer pair, capable of amplifying a 450 base pair fragment directed to a highly conserved region of the viral protein L1.…”
Section: Methodsmentioning
confidence: 99%
“…Despite presenting higher possibility of contamination because the reaction takes place in two steps, nested PCR produced the best amplification results. In a study carried out by Demathe et al (9) , who compared sensitivity in detection of human papillomavirus (HPV) DNA in cases of lip carcinoma in paraffin tissue by PCR and nested PCR, an approximate six-fold increase in detection was verified when nested PCR was used. Confirming these findings, Evander et al (11) also observed an increase using nested PCR in a study on HPV.…”
Section: Discussionmentioning
confidence: 99%